Retrograde jejunogastric intussusception (JGI) with strangulation following previous gastrojejunostomy - Miah, AG; Imam, NA; Joarder, RH; Talukder, SI; Hossain, MS (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):99-101The abstract of this article is available on the PubMed website